1. Art, Technology and Environmental Commitment in Education - Blanco Verónica Perales (Sciendo, 2022)
We believe that it is essential to integrate an ecological analysis in artistic production, or better still, to consider art as a tool and agent towards change. It has never been as necessary as it is right now, and we have never had such a powerful technological device. Technology must be an ally of the planet, or what is the same, of the possibility of life; It has to help us see, hear, and ultimately "feel" better. New technologies have transformed the vision we have of the world and also the representation of it. We are the map and we write it. We are part of the text layer that covers the planet and this layer of information is updated live through each of the nodes that make it up: ourselves. Art and science have tried and try to answer the same basic questions, in this search, and always respecting the precautionary principle, technology is an ally. We feel this common space with an intense latency: art, science and technology, which merge like an image with the coupled layers. Let's hope that from the mixture, sublime not only knowledge, but also wisdom.